Model Pemasaran Digital Banyuwangi-Mall.Com dan Strategi Bersaing UMKM Binaan Tim Rumah Kreatif di Kabupaten Banyuwangi (Digital Marketing Models Banyuwangi-Mall.Com and Competitive Strategies of Msme Creative Home Team Development in Banyuwangi District) - Wibisono, Sigit; Wahyudi, Edy; Wahjuni, Sri (e-Sospol, 2019)
AbstractBan y u w ang i m a ll.c o m is a d i g it a l m a r k e ti n g m od el t ha t s p e c ific a lly m a r k e ts M S ME p r odu cts inB an y u w a n g i Re g e n c y B an y u w ang i m a ll. c o m w a s d e v el op ed in t h e f o r m o f w e b s ite m a r k e ti n g an de d u c a ti o n in na t u r e to M S MEs in B an y u w a n g i Re g e n c y T h e p r ese n ce o f B an y u w ang i M a ll.c o m in t h emi d s t o f d i g it a l bu s i n ess c o m p etiti o n p r o vi d es a view o f t h e b u s i n e s s s t r a te g ies t ha t m u s t b e c a rr ied ou tb y M S MEs in B an y uw ang i Re g e n cy in u til iz i n g an d m a ximiz i n g t h ese f a cilitie s T h is pa p er ba s ic a lly a imsto e xp l a in a n d d esc r i b e t h e m a r k e ti n g m od el o f B an y u w ang i M a ll.c o m an d t h e c o m p etitive s t r a te g ies o fM S MEs a ss i s ted b y cre a tive h o me te a ms in B an y u w ang i Re g e n c y T h is r ese a r ch met ho d u s es a qua litativeapp r oa c h da ta c o llecti o n b y o b s erv a ti o n an d i n d e p th i n tervie w s w ith r e s ou r ce p e r s on s do c u me n t a ti o nan d ab s t r a cti o n p r o c e ss es to s t r e ng t h en da ta a t t h e time o f wr i t i ng T h e c on cl u s i o n in t h is pap er is t h efi r s t abou t t h e d i g it a l m a r k e ti n g m od el in t h e f o r m o f w eb m a r k e ti n g an d e du c a ti o n , t h e s e con d is a b ou tM S ME c o m p etitive s t r a te g ies w h ich c on s i s t o f l o w c o s t s t r a te g ies, d iffe r e n ti a ti o n s t r a te g ies, an d f o c u ss t r a te g ies.Ke y w o r d s B an y u w angi M a ll. C o m, Di g it a l M a r k e ti ng C o m p eti n g S t r a te g ies, M S MEs